Sox2 in the dermal papilla regulates hair follicle pigmentation - Ng, Krystle Joy Tze Hui (Nanyang Technological University, 2022)
Within the hair follicle (HF) niche, dermal papilla (DP) cells are well known for the hair induction capacity; however, DP cell signaling also regulates HF pigmentation. Here we describe how Sox2 in the DP is a key regulator of melanocyte signaling. To study the largely unknown regulatory role the DP has on hair pigmentation, we characterize leptin receptor (Lepr) expression in the skin and as a genetic tool to target the DP. Sox2 ablation in the DP results in a phenotypic switch from eumelanin to pheomelanin. Mechanistically, we describe a temporal upregulation of Agouti and downregulation of Corin, directly by Sox2 in the DP. We also show that bone morphogenic protein (BMP) signaling regulation by Sox2 is responsible for downregulating MC1R, Dct, and Tyr in melanocytes of Sox2 cKO mice. Thus, we demonstrate that Sox2 in the DP regulates not only the choice of hair pigment but also the overall HF pigment production.